2022
DOI: 10.1021/acsmacrolett.2c00556
|View full text |Cite
|
Sign up to set email alerts
|

Tinware-Inspired Aerobic Surface-Initiated Controlled Radical Polymerization (SI-Sn0CRP) for Biocompatible Surface Engineering

Abstract: Surface anchored polymer brushes prepared by surface-initiated controlled radical polymerization (SI-CRP) have raised considerable interest in biomaterials and bioengineering. However, undesired residues of noxious transition metal catalysts critically restrain their widespread biomedical applications. Herein, we present a robust and biocompatible surface-initiated controlled radical polymerization catalyzed by a Sn(0) sheet (SI-Sn 0 CRP) under ambient conditions. Through this approach, microliter volumes of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…On the other hand, it has been demonstrated that the presence of an additional Cu II -based deactivator with respect to that generated through the ATRP equilibrium suppresses irreversible termination reactions. 56,57 In this scenario, SI-Mt 0 CRP could be described by the SARA ATRP mechanism, 56 as the same case of other zerovalent metals, including Fe(0) 43,44 and Sn(0) 4 (Figure 7a and 7b).…”
Section: Plausible Mechanisms For Si-mt 0 Crpmentioning
confidence: 91%
See 4 more Smart Citations
“…On the other hand, it has been demonstrated that the presence of an additional Cu II -based deactivator with respect to that generated through the ATRP equilibrium suppresses irreversible termination reactions. 56,57 In this scenario, SI-Mt 0 CRP could be described by the SARA ATRP mechanism, 56 as the same case of other zerovalent metals, including Fe(0) 43,44 and Sn(0) 4 (Figure 7a and 7b).…”
Section: Plausible Mechanisms For Si-mt 0 Crpmentioning
confidence: 91%
“…Ed.20211331373313737 Tinware-Inspired Aerobic Surface-Initiated Controlled Radical Polymerization (SI-Sn 0 CRP) for Biocompatible Surface EngineeringWuD.YinX.ZhaoY.WangY.LiD.YangF.WangL.ChenY.WangJ.YangH.LuG.LiuX.LiuF.ZhangT. Wu, D. Yin, X. Zhao, Y. Wang, Y. Li, D. Yang, F. Wang, L. Chen, Y. Wang, J. Yang, H. Lu, G. Liu, X. Liu, F. Zhang, T. 10.1021/acsmacrolett.2c00556ACS Macro Lett.2023127176 …”
Section: Key Referencesmentioning
confidence: 99%
See 3 more Smart Citations